Os projetos de colonização e comércio toscanos no Brasil ao tempo do Grão Duque Fernando I (1587-1609) - Holanda, Sérgio Buarque de (2000)
Based on unpublished sources (reproduced at the end of the text) this article examines the comercial activities and the colonization projects in Portuguese America accomplished by Ferdinand I Duke of Toscana at the end of the XVIth and beggining of the XVIIth centuries. It examines also Florence's overseas policies before it became a Principate.